Workplace interventions for intimate partner violence: A systematic review. (3rd July 2019) - Adhia, Avanti; Gelaye, Bizu; Friedman, Lauren E.; Marlow, L. Y.; Mercy, James A.; Williams, Michelle A.
Abstract: Workplace interventions represent important opportunities to increase awareness of and adherence to disease prevention and health promotion initiatives. However, research on workplace interventions for intimate partner violence (IPV) has not been systematically evaluated. This systematic review summarizes existing studies evaluating workplace interventions for IPV. PubMed, PsycINFO, Business Source Complete, Web of Science, and Social Services Abstracts were systematically searched for English-language studies published before November 2017. Six studies evaluating five interventions were included. Only one study used a randomized design, and only two studies measured whether outcomes were sustained over time. None of the interventions addressed perpetrators of IPV. Interventions focused on recognizing signs of abuse, responding to victims, and providing referrals to community-based resources. Methodological rigor of included studies varied, but all reported at least one intervention-related benefit. Findings included improved awareness of IPV, increased provision of information to victims, and greater willingness to intervene if an employee may be experiencing IPV. Although sparse, available evidence suggests there are potential benefits of workplace interventions for IPV. It is important for future interventions to focus on primary and secondary prevention of IPV and address perpetration, and for investigators to use rigorous study designs and measure whether effects are sustained.